Translational research: A patient-centered approach to bridge the valley of death - Thomas, Anish; Desai, Parth; Takahashi, Nobuyuki (Cancer Cell, 2022)
Animal models have evolved to be a key component of translational research of cancer, and they are now extensively used to test drug candidates, predict drug responses, and essentially drive discovery of cancer biology. However, the model-centric approach has not yielded the expected abundance of treatment advances. We propose that the focus of translational research needs to shift from animal models to human patients, and the goal should be to understand why tumor responses and outcomes are so variable between patients and how it can be predicted at the individual level and thus to generate hypotheses that are more relevant to people than to atypically sensitive animal models.